A "family of cycles" – major and auxiliary business cycles. Issue 3 (2014) - Arvydas Jadevicius; Simon Huston
<x xml:space="preserve"> Abstract </x> Purpose – The paper aims to discuss the major and auxiliary types of cycles found in the literature. Design/methodology/approach – The existence of cycles within economy and its sub‐sectors has been studied for a number of years. In the wake of the recent cyclical downturn, interest in cycles has increased. To mitigate future risks, scholars and investors seek new insights for a better understanding of the cyclical phenomenon. The paper presents systematic review of the existing copious cyclical literature. It then discusses general characteristics and the key forces that produce these cycles. Findings – The study finds four major and eight auxiliary cycles. It suggests that each cycle has its own distinct empirical periodicity and theoretical underpinnings. The longer the cycles are the greater controversy which surrounds them. Practical implications – Cycles are monumental to a proper understanding of complex property market dynamics. Their existence implies that economies, whilst not deterministic, have a rhythm. Cyclical awareness can therefore advance property market participants. Originality/value – The paper uncovers four major and eight auxiliary types of cycles and argues their importance. <ack> <x xml:space="preserve"> Acknowledgements </x> An initial version of this paper was presented at the XI BSV International Conference on Valuation and Investment, Minsk, Belarus. The authors would like to thank two anonymous referees for their valuable comments and constructive suggestions. Full responsibility for any errors rests with the authors. </ack>